Studi Komparasi Penggunaan Media Pembelajaran Ular Tangga dengan Flash Card pada Mata Pelajaran Bahasa Indonesia - sugiarti sugiarti; Khosi'in khosi'in (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the differences in the use of snake and ladder media and flash cards in Indonesian language subjects in class V of 67 Elementary Schools in Bengkulu City, which are divided into 2 classes, namely class A and B with 40 students. Researchers took these 2 classes to be the sample, namely the VA class with 20 people as the experimental class and 20 people to the VB class as the control class. This type of research is a quantitative study with an experimental method approach. And data collection techniques using observation, test questions Esay and documentation. Data collection techniques using the t test. It was found that the results of the student poststest class VA who used the snake and ladder learning media were in the medium category, as many as 17 students (85%) got grades 68.4 to 90.6. And the learning outcomes of class VB using Flash Cards learning media as many as 16 students (80%) get scores between 68.1 to 81.9. The results of the study can be concluded that there are differences between the media of snakes and ladders and flash cards on the speaking ability of grade V students in Indonesian subjects at SDN 67 Bengkulu City. With the calculation of the t test where tcount> ttable (2.601> 2.021). Keywords: Media Snakes and Ladders, Media Flash Cards, Talking Ability.